A mechanism for electrostatic solitary waves observed in the reconnection jet region of the Earth's magnetotail - Lakhina, G. S.; Singh, S. V.; Rubia, B. (My University, 2021)
Electrostatic solitary waves (ESWs) have been observed in the reconnection jet region in the Earth’s magnetotail by the Magnetospheric Multiscale spacecraft (MMS). A mechanism for the reconnection jet ESWs is proposed in terms of slow and fast ion-acoustic solitons. At the time of occurrence of ESWs, no hot plasmasheet ions were observed. Based on the observations, the reconnection jet plasma is modeled by a three-component magnetized plasma consisting of hot electrons and two cold ion beams streaming parallel and anti-parallel to the magnetic field, respectively. The model is based on the Sagdeev pseudopotential technique, and it predicts four types of ion-acoustic solitons, namely, two fast and two slow ion-acoustic solitons, where one of each type propagates parallel and another anti-parallel to the ambient magnetic field, respectively. The theoretical model predicts bipolar electric fields with amplitudes in the range of (3–69) mV m−1, positive potentials with amplitudes of (51–539) V, and the soliton widths of (4.5–10.3) Debye lengths. These predictions are in good agreement with the observed characteristics of ESWs in the reconnection jet region.
Keywords: Electrostatic solitary waves; Magnetotail; Solitary waves